2021
DOI: 10.1109/tetc.2019.2902799
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Performance Evaluation of RNS Variants of the BFV Homomorphic Encryption Scheme

Abstract: Homomorphic encryption is an emerging form of encryption that provides the ability to compute on encrypted data without ever decrypting them. Potential applications include aggregating sensitive encrypted data on a cloud environment and computing on the data in the cloud without compromising data privacy. There have been several recent advances resulting in new homomorphic encryption schemes and optimized variants. We implement and evaluate the performance of two optimized variants, namely Bajard-Eynard-Hasan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 24 publications
1
54
0
Order By: Relevance
“…They all target performing a small number of HE Mul without bootstrapping, inhibiting their applicability to a wide range of applications requiring hundreds to thousands of multiplication be performed (e.g., deep learning). GPU implementation studies [4], [7], [8], [22] do not take advantage of the algorithm's internal parallelism sufficiently, operate on only small or limited parameters, or do not consider the cost of modulo operations.…”
Section: Introductionmentioning
confidence: 99%
“…They all target performing a small number of HE Mul without bootstrapping, inhibiting their applicability to a wide range of applications requiring hundreds to thousands of multiplication be performed (e.g., deep learning). GPU implementation studies [4], [7], [8], [22] do not take advantage of the algorithm's internal parallelism sufficiently, operate on only small or limited parameters, or do not consider the cost of modulo operations.…”
Section: Introductionmentioning
confidence: 99%
“…Our work is the first to comprehensively optimize client-side HE cryptographic primitives, which is crucial in client-aided HE. Furthermore, unlike prior work targeting large, high-power GPUs [3,18,54] and FPGAs [46,59,63,70], CHOCO-TACO empirically optimizes for a small ASIC implementation, directly addressing the need for low-power, energy-efficient operation at the client device. Hardware Security.…”
Section: Related Workmentioning
confidence: 99%
“…GPU-based Acceleration. GPU is an alternative computing platform to accelerate evaluation functions [6,21,24,42,48,59]. Wang et al [59] have proposed the first GPU acceleration of FHE that targets Gentry-Halevi [34] scheme.…”
Section: Large-integer Multiplication Hardware Accelerationmentioning
confidence: 99%
“…In [58], a GPU-based implementation of BGV scheme [11] is introduced. In [6], a comprehensive study is reported for multithreaded CPU execution as well as GPU for the BFV scheme. To the best of our knowledge, there is no GPU-accelerated implementation of the CKKS scheme.…”
Section: Large-integer Multiplication Hardware Accelerationmentioning
confidence: 99%